2005
DOI: 10.1007/s11270-005-9003-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Of Pedotransfer Functions Describing Cadmium Sorption In Soils

Abstract: Pedotransfer functions based on general purpose Freundlich isotherms (GPF) were derived for Cd using different combinations of input variables or development conditions. The models match the criterion of flexibility as they were derived from data of 497 soil samples, which had strongly varying soil characteristics. The prediction efficiency of the approaches was investigated by comparison of measured and simulated sorption data for 124 independent soil samples. The parameterisation of the GPF shows that models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In this respect, Koestel and Jorda (2014, n = 558) found that the relative 5% arrival time was strongly dependent on the clay content in a nonlinear fashion. Strong preferential flow was observed for clay contents above 10% but not below this threshold, which roughly coincides with the clay content necessary to form stable soil macrostructures (Horn et al, 2006). Furthermore, the water saturation is fundamental for estimating preferential flow strengths (Jarvis, 2007;Larsbo et al, 2014;Paradelo et al, 2016).…”
Section: Hydraulic Parameterization Of Solute Transportmentioning
confidence: 75%
“…In this respect, Koestel and Jorda (2014, n = 558) found that the relative 5% arrival time was strongly dependent on the clay content in a nonlinear fashion. Strong preferential flow was observed for clay contents above 10% but not below this threshold, which roughly coincides with the clay content necessary to form stable soil macrostructures (Horn et al, 2006). Furthermore, the water saturation is fundamental for estimating preferential flow strengths (Jarvis, 2007;Larsbo et al, 2014;Paradelo et al, 2016).…”
Section: Hydraulic Parameterization Of Solute Transportmentioning
confidence: 75%
“…These indirect relationships have previously been explored in pedotransfer functions (PTFs) [28]. For instance [63,64] demonstrated that various PTFs can be used to predict the adsorption of metals as a function of soil carbon content, CEC and pH. Furthermore, Choe et al (2008) [65] proposed a binding mechanism based on the surface complex model where metals can bind to the hydroxylated mineral surface thus affecting the absorptions characteristic for Fe, Al, Mn oxides and clay minerals or organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Pedotransfer functions estimating the parameters m and b might be useful in estimating C np specific for a given soil with defined soil properties. Pedotransfer functions are physical‐mathematical models, which in the absence of direct measurements, allow estimating of, e.g., soil hydraulic properties (Fila et al, 2006) or soil sorption properties for nutrients (Borggaard et al, 2004), or metals (Horn et al, 2006) from soil data. Pedotransfer functions represent a valuable tool for providing agro‐ecological models with soil input estimations (Fila et al, 2006).…”
Section: Methodsmentioning
confidence: 99%